Kapasitas Pengikatan Iodida dan Iod pada Karbon Aktif Konvensional dan Terbrominasi - Sunarhadijoso Soenarjo; Swasono R. Tamat; Ade Saputra (Fakultas Farmasi Universitas Pancasila, 2005)
Related to the activities in a radioisotope processing laboratory at CDRR, BATAN, active carbon has a great potency and a role as adsorber for radioisotope immobilizing agent in process and installation systems. KAKEN Corporation, a CDRR's collaboration partner in Japan, has introduced a new type of active carbon namely KAKEN Brominated Active Carbon (KBAC) which is claimed to have an anionic exchange character. The presented experiment was thus performed to determine the iodide and iodine binding capacities of the KBAC resin as well as comparing to those of the conventional active carbon, which was also provided by KAKEN (KCAC). The experiment had been done using solutions of natural iodide and iodide - iodine mixtures. The binding capacities were determined by iodometry and iodatometry. In general the results obtained showed that the iodide-binding capacity of KBAC was higher than that of KCAC, but that the iodine-binding capacity of KCAC was higher. The KBAC showed that the binding capacity of iodide from iodide solutions was smaller than that from iodide-iodine samples, while the KCAC showed the reverse.